The raising of predicates predicative noun phrases and the theory of clause structure - Moro, Andrea (Cambridge Univ. Pr., 1997)
The consequences of such a discovery are pervasive. Four distinct areas of syntax are unified into a unique natural class. Along with inverse copular sentences, existential sentences, sentences with seem and unaccusative constructions are analysed as involving the raising of a predicative noun phrase to the most prominent position in the clause structure. In addition, new light is shed on some classical issues such as the distribution and nature of expletives, locality theory, cliticization phenomena, possessive constructions and the cross-linguistic variations of the Definiteness Effect
Keywords: Gezegde; Gramática comparada y general - Frases verbales; Gramática comparada y general - Sintaxis; Nominale constituenten; Propositions (Linguistique); Syntagme verbal; Syntaxe; Zinsconstructies; Grammatik; Grammar, Comparative and general -- Clauses; Grammar, Comparative and general -- Syntax; Grammar, Comparative and general -- Verb phrase; Nominalphrase; Raising; Prädikat